Development of a Motorcycle Parts Search Platform with a Design Thinking Approach - Wayman Anwar; A A B Dinariyana (Jurnal Indonesia Sosial Teknologi, 2024)
In the motorcycle industry, finding spare parts is a big challenge for vehicle owners. This is due to the complexity of the parts market as well as the diverse needs of users. To overcome this challenge, an innovative approach is needed in designing a parts search system that is not only effective but can also meet diverse needs. This research aims to apply the Design Thinking method in designing a motorcycle parts search and gain a deep understanding of the needs and challenges faced by users, as well as create better solutions that are by these needs. This research applies a Design Thinking approach that involves a series of stages such as Empathize, Define, Ideate, Prototype and Test. Data was obtained through direct observation, interviews with related parties, and analysis of existing problems. The results of the study show that the majority of users are men (80%), with the dominance of entrepreneurs (43.3%) and Generation Y (76.7%). The app is also attractive to Bachelor's graduates (43.3%) and users with high needs (53.33%). Important factors that increase the app's benefits include a search feature by name and complete product details. The implementation of motorcycle parts search using Design Thinking is expected to help the company strengthen its brand image as a service provider that is responsive to user needs and increase customer loyalty through a better experience in the parts search process.